Administration of Ligilactobacillus salivarius CECT 30632 to elderly during the COVID-19 pandemic: Nasal and fecal metataxonomic analysis and fatty acid profiling - Mozota, Marta; Castro, Irma; Gómez-Torres, Natalia; Arroyo, Rebeca; Gutiérrez-Díaz, Isabel; Delgado, Susana; Rodríguez, Juan Miguel; Alba, Claudio (Frontiers in Microbiology, 2022)
Elderly was the most affected population during the first COVID-19 and those living in nursing homes represented the most vulnerable group, with high mortality rates, until vaccines became available. In a previous article, we presented an open-label trial showing the beneficial effect of the strain Ligilactobacillus salivarius CECT 30632 (previously known as L. salivarius MP101) on the functional and nutritional status, and on the nasal and fecal inflammatory profiles of elderly residing in a nursing home highly affected by the pandemic. The objective of this post- hoc analysis was to elucidate if there were changes in the nasal and fecal bacteriomes of a subset of these patients as a result of the administration of the strain for 4 months and, also, its impact on their fecal fatty acids profiles. Culture-based methods showed that, while L. salivarius (species level) could not be detected in any of the fecal samples at day 0, L. salivarius CECT 30632 (strain level) was present in all the recruited people at day 120. Paradoxically, the increase in the L. salivarius counts was not reflected in changes in the metataxonomic analysis of the nasal and fecal samples or in changes in the fatty acid profiles in the fecal samples of the recruited people. Overall, our results indicate that L. salivarius CECT 30632 colonized, at least temporarily, the intestinal tract of the recruited elderly and may have contribute to improvements in their functional, nutritional and immunological status, without changing the general structure of their nasal and fecal bacteriomes when assessed at the genus level. They also suggest the ability of low abundance bacteria to train immunity.